Increasing early protein intake is associated with a reduction in insulin-treated hyperglycaemia in very preterm infants. (7th June 2011) - Mahaveer, A; Grime, C; Morgan, C
Abstract : Introduction: A standardised, concentrated neonatal parenteral nutrition (scNPN1) regimen can increase very preterm protein intake.1 Our aim was to compare macronutrient intake and metabolic tolerance using a modified regimen (scNPN2) designed to introduce protein within 4 h of birth. Methods: Local audit committee approval was obtained. 14-day fluid/drug infusion and biochemical data for infants <29 weeks were collected from NICU electronic patient data management systems using the previous methodology. This allowed evaluation of metabolic stability and actual daily parenteral/enteral macronutrient intake to be calculated and compared. Both regimens had identical formulations, intravenous glucose regimens and protocols for managing hyperglycaemia. Results: Infants (n=38): median (range) birthweight 935 g (440–1350) receiving scNPN2 were compared to previous study (n=38): birthweight 890 g (470–1330). No differences in actual daily glucose/carbohydrate, early lipid or enteral intake were identified. scNPN2 regimen increased mean early protein intake (p<0.001) mainly by starting PN soon after birth (p<0.001). This was associated with fewer insulin treated infants (p<0.02) and less insulin usage: The pattern of glucose intolerance (both groups) showed peak insulin use between days 6–9. No violations of the hyperglycaemia treatment protocol were identified. Conclusion: The scNPN2 regimen improved early protein intake as intended. This was associated with a clinically important fall in insulin-treated hyperglycaemia requiring further study.